Do Islamic Banks Contribute to Economic Growth? Evidence from the GCC countries - Bendriouch, Fatima Zahra; Satt, Harit; M’hamdi, Mohamed (International Journal of Economics and Financial Issues, 2020)
The purpose of this study is to examine the existing relationship between Islamic banks’ performance and economic growth in GCC countries. In this quest, this paper attempts to examine whether Islamic banks contribute to the economic growth. We develop a structural equation model to attest these links based on the evidence that Islamic finance contributes to higher levels of economic growth. As a measure of profitability, we include several determinants that are usually ignored in the literature; namely, size, liquidity, capital adequacy, credit risk, and expense management. The study covers Islamic banks operating in Bahrain, UAE, Kuwait, Oman, Qatar and Saudi Arabia over the period 2010 to 2017. We show a positive relationship between Islamic banks and economic growth, especially for the years immediately after the global financial crisis. In other words, Islamic banks performance have contributed to economic growth mainly during the period right after the financial crisis. Our findings represent a significant contribution to explaining how Islamic financial institutions’ activities induce economic growth. Our findings could grant the managers of the Islamic banks a better understanding on how their institutions could improve economic performance as it reduces the severity of the financial crisis by avoiding major weaknesses of the conventional banking system. Keywords: GCC countries, Islamic banks, economic growth, structural equation JEL Classifications: G20; O11 DOI: https://doi.org/10.32479/ijefi.10046